EMPLOYER BRANDING AND WORK ENGAGEMENT IN NON-BANK FINANCING COMPANY - Wardani, Laila Meiliyandrie Indah; Oktafiansyah, Dhoni (Faculty of Psychology, Diponegoro University, 2020)
This research was conducted to determine whether employer branding has a relationship with work engagement in a private company in the field of non-bank financing. The population of this research is the workers of a national private company engaged in the field of non-bank financing, especially the head office workers located in Jakarta. The number of samples of this study were 117 people, consisting of 62 men and 55 women with an age range of 20-67 years (Mean = 28.13; SD = 5.849). The method used is quantitative with stratified sampling technique. The research instrument used was the Employee Attractiveness Scale (EmpAt) (Î± = .956; 20 items). Whereas to measure the Work Engagement using Utrech Work Engagement Scale (UWES) (17 items; Î± = .896). The analysis carried out is a simple linear regression, t-test and one-way ANOVA. The results of this study found that Employer Branding had a significant positive effect on Work Engagement (F (1.115) = 50.333; Î² = .552, r = .552; R2 = .304; P <.001). Employer branding can be a strategy for companies to identify the needs of current and future workers, and build an image as a company of choice for work, so as to increase employee engagement with the company and its work.